DECISION TREES IN CLASSIFICATION TASKS - Stirna, Lauris; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The goal of the study is to develop a classification system for Iris dataset. The analytical development environment called KNIME and freely available Iris dataset were applied in the research. The developed classification is based on the decision tree application. The accuracy of decision tree is compared with artificial neural network.